Effects of Ni Content on Melting Behaviors and Wettability of SnBiAgNi Lead-Free Solder - Niwat Mookam; Prajak Jattakul; Kannachai Kanlayasiri (Materials science forum, 2022)
This research aimed to study the effects of Ni content on melting behaviors and wettability of SnBiAgNi lead-free solder. Sn-58Bi-0.05Ag was used as the base solder, and Ni was then put in by 0.05, 0.10, 0.50 or 1.00 wt%. Solidus and liquidus temperatures of the solder alloys were examined to study melting behaviors. The Ni content changed the solidus and liquidus temperatures, and Sn-58Bi-0.05Ag-0.10Ni possessed the lowest solidus and liquidus temperatures. Sn-58Bi-0.05Ag-0.10Ni also provided the narrowest pasty range. Wettability of the solders on the copper substrate was expressed in terms of spread factor. The addition of Ni improved the wettability of the base solder, and Sn-58Bi-0.05Ag-0.10Ni provided the highest spread factor.
Keywords: Electronic Packaging and Soldering Technologies; 3D IC and TSV technologies; Intermetallics and Advanced Alloy Properties